Isolation of Morganella morganii and Staphylococcus aureus in a canine patient with skin and soft tissue injury: Case report - Maldonado Vera, María Camila (2021)
The clinical case of a canine with deep ulcerative pyoderma with dermal necrosis is presented, where Morganella morganii and Staphylococcus aureus were isolated from the skin lesions. The first is a bacterium from the environment and in the normal flora of the intestinal tract, and rarely reported in canines. S. aureus is a recognized gram-positive staphylococcal bacterium that is associated with suppurative infections. The results that address this study indicate the importance of carrying out a rapid recognition, diagnosis and initiation of treatment based on cultures and antibiograms. Polymicrobial infection makes treatment and its evolution difficult, and the progression of skin lesions and secondary systemic diseases must be avoided.